Colonies of the fungus Aspergillus niger are highly differentiated to adapt to local carbon source variation. (6th January 2020) - Daly, Paul; Peng, Mao; Mitchell, Hugh D.; Kim, Young‐Mo; Ansong, Charles; Brewer, Heather; de Gijsel, Peter; Lipton, Mary S.; Markillie, Lye Meng; Nicora, Carrie D.; Orr, Galya; Wiebenga, Ad; et al.
Summary: Saprobic fungi, such as Aspergillus niger, grow as colonies consisting of a network of branching and fusing hyphae that are often considered to be relatively uniform entities in which nutrients can freely move through the hyphae. In nature, different parts of a colony are often exposed to different nutrients. We have investigated, using a multi‐omics approach, adaptation of A. niger colonies to spatially separated and compositionally different plant biomass substrates. This demonstrated a high level of intra‐colony differentiation, which closely matched the locally available substrate. The part of the colony exposed to pectin‐rich sugar beet pulp and to xylan‐rich wheat bran showed high pectinolytic and high xylanolytic transcript and protein levels respectively. This study therefore exemplifies the high ability of fungal colonies to differentiate and adapt to local conditions, ensuring efficient use of the available nutrients, rather than maintaining a uniform physiology throughout the colony.